Difference and proliferation: race in the poetry of Elizabeth Bishop = Diferença e proliferação: o conceito de raça na poesia de Elizabeth Bishop - Terry Caesar (Acta Scientiarum: Language and Culture, 2010)
The current paper deals with the whole imagination of race in the work of a major American poet. The very subject of race intersects with the question of national identity, also neglected in Bishop’s work, although not in the same way. The aim of the discussion is to align the racial text with the national text. How can we understand Bishop’s consistent interest in race throughout her poetry, and what effect can be observed in it as a result of her exposure to racial constructs in Brazil that are so different from those of her native United States? We can see this effect manifest even in the controversy over her 1965 magazine article on the quatercentenary of Rio de Janeiro. What does this controversy demonstrate, finally, but that national experience with respect to race turns out to be mutually exclusive? One cannot be in this respect both Brazilian and American—in prose. In poetry, however, it is quite another matter. The subject of race is all of a piece, and has been all along conducted in Bishop’s work according to a logic ultimately apart fromnational construction. Analisa-se a imaginação de raça na obra de Elizabeth Bishop, uma poetisa importante da literatura estadunidense. O assunto ‘raça’ cruza com o problema da identidade nacional, também negligenciado na obra de Bishop, embora de modo diferente. A presente discussão alinha o texto racial ao texto nacional. Como pode-se compreender o seu interesse constante sobre ‘raça’ e quais são os efeitos em sua poesia como resultado de sua exposição às construções raciais no Brasil, as quais são tão diferentes daquelas nos Estados Unidos? Este efeito manifesta-se também em seu artigo numa revista de 1965 referente ao quatrocentenário do Rio de Janeiro. Esta controvérsia parece mostrar que a experiência nacional sobre ‘raça’ é mutuamente exclusiva. Na prosa não se pode ser brasileiro ou estadunidense ao mesmo tempo. Na poesia, parece que os parâmetros são diferentes. O problema deve ser abordado em sua totalidade e, na obra de Bishop, tem sido conduzido de acordo com uma lógica desligada da construção nacional.